Promoting harmony and renewal: The transformation of peace education within the islamic education curriculum - Atsani, Lalu Gede Muhammad Zainuddin; Hadisaputra, Prosmala (Univeritas Papua, 2024)
This article examines the development of peace education within the context of the Islamic education curriculum. This study aims to enhance the concept of peace education by drawing on prior research. This study adopts a qualitative approach, utilizing literature review techniques. Despite being classified as a literature review, the study was conducted in phases to achieve significant results. First, an extensive review of existing literature was conducted. Second, a comprehensive search was performed on Google Scholar to identify relevant scholarly sources. Third, a meticulous screening of documents was carried out to select the most pertinent ones for analysis. Fourth, the process of importing the accumulated material into the Mendeley software and subsequently arranging it in a systematic manner. Fifth, the utilisation of scanning techniques for the purpose of reading books is seen. Sixth, the identification and underlining of words or sentences that serve as indicators of the underlying theme of the study. Seventh, the themes identified in the previous step are to be mapped out in a specific and detailed manner. This study demonstrates that peace education can be implemented in educational curriculum through different approaches, such as curricula centred around dialogue, education that emphasises values, programmes targeting the enhancement of life skills for individuals affected by post-conflict situations, adjustments to the national curriculum, and curricula that promote multiculturalism. The findings of this study enhance the conceptual framework of peace education.